The Effect of Using Spinning Wheel Media on the English Learning Outcomes of Class III Students at SD Inpres Fatukoa, Kupang City - Tukan, Eugenesia Elisabet; S. Tanggur, Femberianus; E Noya Nahak, Kristina (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Learning English is an important process to help students develop their English language skills from an early age. The lessons on “things in the classroom” is used as one of the topics researched the KKM score. The third graders of SD Inpres Fatukoa Kota Kupang City were the subjects of this research, which set out to quantify the impact of using revolving sheel media on test scores. This studi used a quasi-experimental methodology resembling a nonequivalent control group design. It was administered 47 students and collected data via observasion, multitiple-choice tests, and image matching as well as using test instruments and observation sheets. Tests of hypotheses and t-tests were used to appraise the data. Based on the t-test findings, there was a 24,9 point difference between the experimental and control classes’ average post-test scores:87,61>62,71. Furthermore, the Independent Samples Test, which is used for hypothesis testing, reveals that a significance level of 0.000 < 0,05 in the 2-tailed t-test for equality of means indicates that the null hypothesis(H0) is rejected and the alternative hypothesis(Ha) is accepted. We may thus infer that third graders at SD Inpres Fatukoa Kupang City benefit greatly from using spinning wheel media to improve their English language ability.